CELLISA: a rapid and reliable method for primary screening of hybridoma supernatant for cell surface antigens - Chong, Chou Min; Than, Leslie Thian Lung; Shamsudin, Mariana Nor; Md. Yusoff, Fatimah; Abdullah, Maha (2012)
Cell surface markers are particularly important in immunology to identify and differentiate the many different types and stages of cells that respond to foreign intervention including infecting pathogens. These are especially lacking in the field of veterinary science. Specific monoclonal antibodies are produced via the hybridoma technology. Rapid and sensitive assays are crucial in preliminary screening as early hybridoma clones only secrete low amounts of antibodies. A cell-based enzyme-linked immunosorbent assay (CELLISA) is described for the primary screening of hybridoma supernatants. Time is saved as whole cell suspensions of lymphocyte, adherent cell like macrophages and fragile cells like erythrocytes and granulocytes are directly coated, without modification, to plates. The methodology is adaptable to be employed to a variety of different cell types with no or little alteration of surface antigens.